Germany's Short Time Compensation Program: macroeconom(etr)ic insight - Henner Will (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
Short Time Compensation [STC] was a key program in Germany to fight the crisis. However, STC is quite an old tool: in the past 100 years it has been used quite often and is very multifunctional. It stabilized employment in every kind of macroeconomic shock. After a brief look into the institutional and quantitative development of STC in Germany, this paper tries to answer the question whether STC prevents Schumpeterian creative destruction and structural change in economic downturns. With the help of a VAR-Model we can analyze interdependencies between the business cycle, STC and unemployment, finding evidence for a bridging function of STC. A closer look at the pro-cyclical average stoppage supports the thesis that most of the enterprises using STC are fundamentally economically healthy, that is, STC does not prevent structural change in downturns.
urn:nbn:de:101:1-201202285141
Keywords: E24; E32; C32; J38; N44; 330; Short Time Compensation; VAR; Paradox; structural change; Unterbeschäftigung; Arbeitsmarktpolitik; Makroökonomischer Einfluss; Strukturwandel; Schätzung; Deutschland